+0  
 
0
594
1
avatar

7x + 10 - ( x+ 7 ) =

 Feb 1, 2015

Best Answer 

 #1
avatar+95360 
+5

7x + 10 - ( x+ 7 ) =

there is an invisable 1 between the minus sign and the backet.

7x + 10 - 1( x+ 7 ) =

Now the minus sign belongs to the 1

-1(x+7)=-1*x+-1*7 = -x-7

so   

   7x + 10 - ( x+ 7 )

=7x+10     -x-7

=7x-x   +10-7

=6x     +3

 Feb 2, 2015
 #1
avatar+95360 
+5
Best Answer

7x + 10 - ( x+ 7 ) =

there is an invisable 1 between the minus sign and the backet.

7x + 10 - 1( x+ 7 ) =

Now the minus sign belongs to the 1

-1(x+7)=-1*x+-1*7 = -x-7

so   

   7x + 10 - ( x+ 7 )

=7x+10     -x-7

=7x-x   +10-7

=6x     +3

Melody Feb 2, 2015

35 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.